Joint Modulations of Electromagnetic Waves and Digital Signals on a Single Metasurface Platform to Reach Programmable Wireless Communications. (January 2022) - Wan, Xiang; Xiao, Chaokun; Huang, He; Xiao, Qiang; Xu, Wei; Li, Yueheng; Eisenbeis, Joerg; Wang, Jiawei; Huang, Ziai; Cheng, Qiang; Jin, Shi; Zwick, Thomas; et al.
Abstract: In current wireless communication and electronic systems, digital signals and electromagnetic (EM) radiation are processed by different modules. Here, we propose a mechanism to fuse the modulation of digital signals and the manipulation of EM radiation on a single programmable metasurface (PM). The PM consists of massive subwavelength-scale digital coding elements. A set of digital states of all elements forms simultaneous digital information roles for modulation and the wave-control sequence code of the PM. By designing digital coding sequences in the spatial and temporal domains, the digital information and far-field patterns of the PM can be programmed simultaneously and instantly in desired ways. For the experimental demonstration of the mechanism, we present a programmable wireless communication system. The same system can realize transmissions of digital information in single-channel modes with beam-steerable capability and multichannel modes with multiple independent information. The measured results show the excellent performance of the programmable system. This work provides excellent prospects for applications in fifth- or sixth-generation wireless communications and modern intelligent platforms for unmanned aircrafts and vehicles.